ANALISIS POTENSI DAN KENDALA PENGEMBANGAN ASURANSI SYARIAH DI KOTA MEDAN - Rizki Redhika; Kasyful Mahalli (Ekonomi dan Keuangan, 2014)
This research entitled "Potential and Obstacle Analysis of Syaria’ Insurance Expansion in Medan" intended to know the internal factors such as strength and weakness and the external factors such as opportunity and threat of syaria' insurance in Medan. The type of data used is primary and secondary data. The primary data was taken from a direct interview with the chairman of PT. Asuransi Takaful Umum Cabang Medan. The secondary data was taken from books, Takaful Umum annual report, websites, essays, and other media. Data analysis method used is descriptive method which used SWOT analysis data. The estimation result shows that PT. Asuransi Takaful Umum Cabang Medan is in the first quadrant which means positive by supporting the aggresive growth strategy using SO strategy that using all reliable power and utilize opportunity well.Keywords: Potential, Obstacle, SWOT analysis, and Syaria’ Insurance.